2021
DOI: 10.1093/femsle/fnab050
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antimicrobial, antioxidant and cytotoxic activity of the essential oil from the leaves of Stachys pilifera Benth

Abstract: Stachys pilifera Benth is an endemic species of Stachys family found in Iran with a wide application as an herbal tea. The objective of this research was to evaluate the antimicrobial, antioxidant, and cytotoxic activity of the essential oil from the aerial parts of S. pilifera. Essential oil (EO) composition analysis showed that cis-Chrysanthenyl acetate (24.9%), viridiflorol (18.3%), trans-Caryophyllene (9.8%), caryophyllene oxide (4.6%), α-terpineol (3.3%), and linalool (3.1%) were the most abundant compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Various studies have identified over 30 compounds in the essential oil of S. pilifera . Composition studies of essential oils of S. pilifera revealed the most prevalent components to be cis-chrysanthenyl acetate (24.9% ), viridiflorol (18.3%), trans-caryophyllene (9.5% ), caryophyllene oxide (4.6% ), α -terpineol (3.3%), and linalool (3.1%) [ 28 ]. In another study, cis-chrysanthenyl acetate (24.9%), viridiflorol (18.3%), trans-caryophyllene (9.8%), caryophyllene oxide (4.6%), terpineol (3.3%), and linalool (3.1%) were detected in the EO of S. pilifera [ 29 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have identified over 30 compounds in the essential oil of S. pilifera . Composition studies of essential oils of S. pilifera revealed the most prevalent components to be cis-chrysanthenyl acetate (24.9% ), viridiflorol (18.3%), trans-caryophyllene (9.5% ), caryophyllene oxide (4.6% ), α -terpineol (3.3%), and linalool (3.1%) [ 28 ]. In another study, cis-chrysanthenyl acetate (24.9%), viridiflorol (18.3%), trans-caryophyllene (9.8%), caryophyllene oxide (4.6%), terpineol (3.3%), and linalool (3.1%) were detected in the EO of S. pilifera [ 29 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…A study revealed that EO of S. pilifera had lower minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against Gram-positive bacteria ( Bacillus cereus and Staphylococcus aureus ) than Gram-negative bacteria ( Staphylococcus aureus and Bacillus subtilis ) ( Shigella sonnei, Escherichia coli, Salmonella enterica subsp. enterica, and Pseudomonas aeruginosa ) [ 28 ]. Farjam et al studied the activities of the n-butanolic extract of S. pilifera against Gram-positive and Gram-negative bacteria and fungi.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 2 more Smart Citations